Analisis Kualitas Pembelajaran IPA Melalui Penerapan Model Pembelajaran Problem Based Learning (PBL) di Sekolah Dasar - Hesti Indriani (RUKASI: Jurnal Ilmiah Perkembangan Pendidikan dan Pembelajaran, 2025)
The development of the implementation of the problem-based learning (PBL) model has significantly increased over the past six year, with the impact of using the model on science learning outcomes being particularly popular in both junior high and senior high schools, especially elementary schools. There has been an increase in research, including theses and SINTA articles, related to this topic. The aim of this study is to determine the extent to which the use of the problem-based learning model influences science learning outcomes in elementary schools. A Systematic Literature Review (SLR) methodology was employed in this study. This methodology allows for the examination and synthesis of recent findings in elementary education. Using the PRISMA methodology, this study conducted steps such as identification, screening, feasibility assessment, and inclusion criteria. The sources of literature, covering the years 2019 to 2024, were obtained from Google Scholar database. The conclusion of this study comes from the database search using keywords such as science learning quality, the implementation of problem-based learning (PBL), and elementary schools. After completing the literature search, the analysis resulted in ten articles that met the requirements to be included in a detailed analysis. These articles were then selected and included. To ensure that students achieve the highest academic success, the application of the appropriate model in science learning in elementary schools classrooms can have a positive impact on the learning process.